Application of USLE and GIS to predict erosion loss at Brantas Watershed - Indarto Indarto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
Erosion processes are still the dominant factor affecting land degradation. The rapid calculation of erosion loss is urgently required for conservation planning and management at the watershed level. This paper is reporting the use of USLE method and GIS at Brantas Watershed. The digital layer data of rainfall from 2005 to 2014, soil types, land use, and DEM (from ASTER GDEM2) were used as the main input. The research procedures consist of (1) data inventory dan preparation, (2) calculation of the erosion factors (R, K, LS, CP), and (3) calculation and classification of the erosion hazard. The erosivity factor (R) is calculated from the analysis of annual rainfall data. The erodibility factor (K) is obtained using analysis of soil type map. The length and slope factor (LS) is calculated from the DEM and Soil layer data. The crop cover and conservation activities (CP) is interpreted from RBI maps year 2014. The results showed that the erosion hazard in Brantas Watershed dominated by very low with predominantly the erosion yield of 0,96 ton/ha/year. Thus required conservation and watershed management activities to prevent an increase erosion hazard in the Brantas Watershed.Keywords: erosion yield, USLE, GIS, Brantas, Watershed